1997
DOI: 10.1093/carcin/18.2.423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle exposure and particle-elicited inflammatory cells on mutation in rat alveolar epithelial cells

Abstract: To investigate mechanisms underlying development of lung adenomas and carcinomas in rats exposed to poorly soluble particles the relationships between particle exposure, inflammation and mutagenesis in rat alveolar type II cells were characterized. Rats were exposed to saline or saline suspensions of 10 and 100 mg/kg of alpha-quartz, carbon black or titanium dioxide by intratracheal instillation. Fifteen months after exposure, bronchoalveolar lavage (BAL) cells were characterized as to number and type and lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
125
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(141 citation statements)
references
References 7 publications
8
125
1
Order By: Relevance
“…The data confirm findings according to which BAL cells of exposed rats (exposure to carbon black or titanium dioxide) caused mutations in the Hprt gene after in vitro incubation together with alveolar type II rat cells (cell strain: RLE-6TN) (Driscoll et al 1997). Like α-quartz, carbon black and titanium dioxide induced epithelial hyperplasia in the rat lung.…”
Section: Concerning 3)supporting
confidence: 86%
See 1 more Smart Citation
“…The data confirm findings according to which BAL cells of exposed rats (exposure to carbon black or titanium dioxide) caused mutations in the Hprt gene after in vitro incubation together with alveolar type II rat cells (cell strain: RLE-6TN) (Driscoll et al 1997). Like α-quartz, carbon black and titanium dioxide induced epithelial hyperplasia in the rat lung.…”
Section: Concerning 3)supporting
confidence: 86%
“…DNA damage and mutations follow. Mutations, induced by the oxidants released by inflammatory cells, have been identified in both co-cultivated bacteria and mammalian cells (Driscoll et al 1997;Evans et al 2004;Jackson et al 1989;Weitzman and Stossel 1981). By incubating polymorphonuclear leukocytes of humans together with alveolar type II epithelial cells of rats, it was possible to demonstrate that the reactive oxygen species released by leukocytes reach the genome of the epithelial cells, where they induce premutagenic 8-oxo-2'-desoxyguanine adducts (Knaapen et al 1999).…”
Section: Concerning 3)mentioning
confidence: 99%
“…The exposure of peripheral human lymphocytes to TiO 2 NPs can lead to the activation of DNA damage check points and accumulation of tumour suppressor protein p53 (Kang et al 2008). In vitro and in vivo studies of different experimental models showed that nanoTiO 2 could cause genotoxic effects through indirect mechanisms like oxidative stress and inflammation (Driscoll et al 1997;Xu et al 2008;Trouiller et al 2009;Petković et al 2011). ROS are important signalling molecules that can affect cell proliferation, inflammation and cell death (Sha et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ozone caused lung tumors in mice, with a high frequency of K-ras mutations including G to T transversion in codon 12 (Sills et al, 1995). Alveolar type II cells in rat lungs exposed intratracheally to inorganic particles, resulting in neutrophil and macrophage in®ltration, showed a large increase in HPRT mutations (Driscoll et al, 1997).…”
Section: Discussionmentioning
confidence: 99%